JJ Mak Pon / Nuraihan Ridzuan, Madihah Husna Rosli, Nur Syafiqah Sariff, Amidathul Najwa Hussin, Siti Suraya Mohd Idris and Nur Hafiza Jebat - Ridzuan, Nuraihan; Rosli, Madihah Husna; Sariff, Nur Syafiqah; Hussin, Amidathul Najwa; Mohd Idris, Siti Suraya; Jebat, Nur Hafiza
Mee Bandung or Mee Bandung Muar is a traditional Southeast Asian cuisine which is this dish originated from Muar, Johor, Malaysia. The word "Bandung" is derives from the literal meaning of the word in Masry language which if roughly translates as moved or paired. Many people had misconception that think the name "Mee Bandung” originated from the Indonesia Country which is Bandung Cry, which leads the terms "Bandung" and these "Bandung City” is unrelated at all.